2000
DOI: 10.1080/09629350020025755
|View full text |Cite
|
Sign up to set email alerts
|

Permeability characteristics of human endothelial monolayers seeded on different extracellular matrix proteins

Abstract: OBJECTIVE: To investigate whether endothelial monolayer permeability changes induced by inflammatory mediators are affected by the extracellular matrix protein used for cell seeding. METHODS: Human umbilical venular endothelial cells (HUVEC) were grown to confluent monolayers on membranes coated with either collagen, fibronectin or gelatin. The permeability to albumin and dextran was then assessed, both under normal conditions and after treatment with tumor necrosis factor-alpha (TNF-alpha) and bacterial lipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 27 publications
3
34
0
Order By: Relevance
“…The mechanisms through which cytokines exert their acute effects on the endothelium to increase its permeability are not fully understood. Studies on models of endothelial monolayers in vitro have suggested that multiple mechanisms are involved, including Ca 2ϩ signaling, endothelial cell contraction with retraction of cells, and changes in intercellular junctions, producing interendothelial gaps (40). Cytokines are also thought to induce production of several other inflammatory mediators and to activate enzymes.…”
Section: Stokes-einstein Radius (å)mentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms through which cytokines exert their acute effects on the endothelium to increase its permeability are not fully understood. Studies on models of endothelial monolayers in vitro have suggested that multiple mechanisms are involved, including Ca 2ϩ signaling, endothelial cell contraction with retraction of cells, and changes in intercellular junctions, producing interendothelial gaps (40). Cytokines are also thought to induce production of several other inflammatory mediators and to activate enzymes.…”
Section: Stokes-einstein Radius (å)mentioning
confidence: 99%
“…Ex vivo studies have shown that endothelial permeability can increase by exposing endothelial cells to TNF-␣ or IL-1␤ (14,34,40,43). IL-6 has also been shown to increase endothelial permeability through alterations of tight junctions, and by rearrangement of intracellular F-actin and changes in cell shape (21,35), which, however, could not be confirmed in other studies (14).…”
mentioning
confidence: 99%
“…Monolayers of human endothelial cells forming the innermost layer of vessels presents a biological barrier to permeation of liquid, proteins, and solutes from the intravascular compartment to the interstitium [2,3]. The vascular endothelium is composed of a monolayer of vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the interaction between cell adhesion molecules (CAMs) and endothelial cells can contribute to pro-inflammatory responses by recruiting monocytes to the injury sites [3]. Inflammatory mediators, such as thrombin, bradykinin, histamine, lipopolysaccharide (LPS), and others, upon binding to their receptors, disrupt the organization of inter-endothelial junctions, thereby opening the junctional barrier [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ECs from different tissue origins, such as LSEC-1, HMEC-1, or HPMEC-ST1.6R, which may have different characteristics, responded differently to DENV infection (9,15,31,32). In the present study, primary HUVECs isolated from normal human umbilical vein were evaluated because they are more relevant to the pathophysiology of DHF/DSS and the most commonly used model to investigate macromolecule transport (33,34). Here we showed that all DENV-2 strains were able to infect ECs and replicate actively (Fig.…”
Section: Discussionmentioning
confidence: 99%